Frequency of chondrocalcinosis of the knees in asymptomatic hyperuricaemia and rheumatoid arthritis: a controlled study. Issue 4 (August 1982) - Hollingworth, P; Williams, P L; Scott, J T
Abstract : An association has been reported between urate gout and chondrocalcinosis. Chondrocalcinosis was detected in knee radiographs of 8 of 138 gouty patients compared with none of 142 age matched nongouty normouricaemic controls (p less than 0.025). To define this association further, knee radiographs were examined of 84 patients with asymptomatic hyperuricaemia who had been carefully age matched with the gouty and control groups. Chondrocalcinosis of the knees was detected in only one patient, the difference from the control group not being significant. It therefore appears that there is an association of chondrocalcinosis with gouty arthritis, but not with asymptomatic hyperuricaemia. An association between chondrocalcinosis and rheumatoid arthritis has been suggested, but the studies were not controlled for age. To re-examine this implied association, knee radiographs were inspected of 127 patients with rheumatoid arthritis who had been age matched with the control group. Chondrocalcinosis of the knees was detected in only one patient, a difference from the control group which is not statistically significant.